Fundamentals of liquid crystal devices. - Yang, Deng-Ke, ....-; Wu, Shin-Tson, ....- (Chichester : Wiley, 2006)
Liquid crystal physics -- Propagation of light in anisotropic optical media -- Optical modeling methods -- Effects of electric field on liquid crystals -- Freedericksz transition -- Liquid crystal materials -- Modeling liquid crystal director configuration -- Transmissive liquid crystal displays -- Reflective and transflective liquid crystal displays -- Liquid crystal display matrices, drive schemes, and bistable displays -- Liquid crystal/polymer composites -- Tunable liquid crystal photonic devices.
Keywords: LCD (Liquid Crystal Displays).